A preliminary survey of prostitution in Kuching / Hew Cheng Sim - Hew, Cheng Sim (Institut Teknologi Mara Cawangan Sarawak, 1990)
The increasing problem of prostitution in the State led to the formation of a Task Force by the Women's Bureau under the Ministry of Social Development in Sarawak. The Task Force was asked to study the problem of prostitution and make recommendations to the various Government agencies in order to better monitor and control the situation. This preliminary survey of prostitution in Kuching was conducted as result of the work of the Task Force. Due to the constraint of time and resources, only a limited number of prostitutes in Kuching were interviewed.